Possibilities and Determinants of Using Low-Cost Devices in Virtual Education Applications. Issue 2 (2017) - Buń, Paweł Kazimierz; Wichniarek, Radosław; Górski, Filip; Grajewski, Damian; Zawadzki, Przemysław; Hamrol, Adam
No abstract available